Geometrical and physicochemical considerations of the pit membrane in relation to air seeding: The pit membrane as a capillary valve - Meyra, Ariel Germán (2007)
A theoretical treatment of some of the factors influencing air seeding at the pit membranes of xylem vessels is given. Pit membrane structure, viewed as a three-dimensional mesh of intercrossing fibrils, and vulnerability to water-stress-induced air seeding are examined in the context of the Young-Laplace equation. Simple geometrical considerations of the porous membrane show that the vapor-liquid interface curvature radius is a function of fiber-fiber distance, fiber radius, wetting angle and position of the wetting line. Air seeding (maximum pressure) occurs at the minimum curvature radius, therefore air seeding is not simply determined by the fiber-fiber distance but is a function of the geometry of the pit membrane and of physicochemical quantities like surface tension and wetting angle. As a consequence of considering a wetting angle different from zero, the minimum curvature radius becomes larger than half the fiber-fiber distance. The present model considers that, for a given pressure difference at the pit membrane, all local interface curvatures are the same. In this sense, pit membranes work as variable capillary valves that allow or prevent air seeding by adjusting local curvatures and interface positions relative to the pore-forming fibers, following the pressure differences across the membranes. The theoretical prediction for the air seeding threshold is consistent with recent experimental data for angiosperm trees.